Human and mouse granzyme A induce a proinflammatory cytokine response - Metkar, Sunil; Menaa, Cheikh; Pardo, Julian; Wang, Baikun; Wallich, Reinhard; Freudenberg, Marina; Kim, Stephen; Raja, Srikumar M.; Shi, Lianfa; Simon, Markus M.; Froelich, Christopher J. (Immunity, 2008)
Granzyme A (GzmA) is considered a major proapoptotic protease. We have discovered that GzmA-induced cell death involves rapid membrane damage that depends on the synergy between micromolar concentrations of GzmA and sublytic perforin (PFN). Ironically, GzmA and GzmB, independent of their catalytic activity, both mediated this swift necrosis. Even without PFN, lower concentrations of human GzmA stimulated monocytic cells to secrete proinflammatory cytokines (interleukin-1beta [IL-1beta], TNFalpha, and IL-6) that were blocked by a caspase-1 inhibitor. Moreover, murine GzmA and GzmA(+) cytotoxic T lymphocytes (CTLs) induce IL-1beta from primary mouse macrophages, and GzmA(-/-) mice resist lipopolysaccharide-induced toxicity. Thus, the granule secretory pathway plays an unexpected role in inflammation, with GzmA acting as an endogenous modulator.